TEACHING READINESS ANALYSIS OF PRESERVICE PRIMARY TEACHERS IN PHYSICAL EDUCATION THROUGH MICROTEACHING - Widiastuti Widiastuti; Oce Datu Appulembang; Lastiar Roselyna Sitompul (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Microteaching serves as a scaled-down teaching practice platform designed to hone fundamental instructional skills among preservice primary teachers. Delivering physical education at the primary level demands specialized competencies distinct from other subjects, given its inherent movement-based nature and outdoor implementation requirements. This study examines the readiness of preservice primary teachers to teach physical education through microteaching activities. Employing a quantitative descriptive approach, we analyzed physical education microteaching assessment data from 28 preservice primary teachers (February-May 2025), evaluating eight core teaching competencies. Results revealed a tripartite competency distribution: High Achievers (16 students): Demonstrated comprehensive mastery of essential microteaching skills, including creative lesson delivery and adaptive classroom management. Intermediate Performers (10 students): Exhibited foundational competence but required refinement in questioning techniques, time management, and instructional transitions. Developing Practitioners (2 students): Showed significant gaps in lesson preparation and teaching confidence, necessitating targeted intervention. The findings underscore two critical implications for teacher preparation: First, most candidates achieved teaching readiness through structured microteaching experiences, validating its efficacy in skill development. Second, the identified competency gaps—particularly in pedagogical content knowledge and self-efficacy-highlight the need for differentiated training approaches. This research emphasizes the indispensable role of microteaching in equipping future elementary teachers with the unique skill set required for effective physical education instruction